ANALISIS SISTEM PENGENDALIAN INTERN SEBELUM DAN SESUDAH PENERAPAN SIMAK BMN PADA TINGKAT UNIT AKUNTANSI KUASA PENGGUNA BARANG DI LINGKUNGAN PANGKALAN TNI ANGKATAN LAUT BANTEN - Arifin, Wiwin; Wulandari, Ayu (JAK (Jurnal Akuntansi) : Kajian Ilmiah Akuntansi, 2014)
If we are given money by their parents to buy the goods, would be asked to buy anything. It will normally occur discussion on whether or not the goods are purchased. After agreeing the goods are purchased, the next question is how and where to buy. Similarly, after the goods purchased would be held accountable. The same process was also carried out in government procurement. Even more complicated and lengthy bureaucracy. Once the goods are purchased will also mean increasing the number of the country's wealth. Next is to manage things as state property. The problem in this study was to determine the results of the internal control system before and after the implementation of SOA environment SIMAK Navy Banten. The author uses descriptive method of analysis that is by gathering evidence and information necessary for the other dat then processed and analyzed up to one conclusion. In addition, the authors also used the method of verification analysis is the analysis of the data by comparing the data according to the needs of the research. Population and the study sample were 30 personnel only, because in this case that did work activity directly related to the internal control system before and after penerapa accounting and management information systems property of the state (SIMAK BMN). The results of hypothesis in this study are very well influence the internal control system (SPI) before and after the implementation of management information systems and accounting property of the state (SIMAK BMN) in Banten Lanal operate. This means that there is a change between the variables before and after the application of SOA towards SIMAK very good. To determine the rate of change of the t value significant level (0231> 0.05)